Synthesis and Anticonvulsant Activity of Some New Dioxolane Derivatives - Özkanlı, Fügen; Güney, Ahu; Çalış, Ünsal; Uzbay, Tayfun (Arzneimittelforschung, 2003)
In this study, ten 2-acetylnaphthalene derivatives with a dioxolane structure were synthesized and screened for their anticonvulsant activities. Dioxolane derivatives were prepared by the reaction with appropriate ethanone, glycol and p-toluensulphonic acid. The structures of the compounds were elucidated by IR, 1H-NMR and elemental analysis. Anticonvulsant activities of the compounds were determined by maximal electroshock seizure (MES) test and subcutaneous metrazol (ScMet.) test. The rotarod toxicity test was used for the assessment of neurological deficits. According to the activity studies compound 6 was found neurotoxic, compounds, 1, 4, 5, 7–9 were found protective against MES and 7–10 were found protective against ScMet. Compounds 2 and 3 were found inactive.
Keywords: 2-Acetylnaphthalene derivatives; Antiepileptic drugs; Dioxolanes, anticonvulsant activity, synthesis